The Basic Components of Software-Hardware System for Modeling and Control of the Toroidal Plasma by Epsilon-Nets on Heterogeneous Mini-Supercomputers (Communications in Computational Physics, 2018)
A significant step towards the comprehensive solution of the important newfundamental control problems of high-temperature plasma of toroidal configuration ismade by utilizing heterogeneous mini-supercomputers of NIISI RAS (Scientific Research Institute of System Development, Russian Academy of Science). The basic components of hardware and software modeling system and automatic real-time plasmafeedback control are developed and implemented. The system is named HASP CS(Hardware-Software Plasma Control System). It is based on a fundamentally new,more accurate and reliable control algorithm using a solution with a given accuracyof a number of inverse diagnostic problems by $ϵ$-nets. The possibility of an application of the proposed technique during discharge time to provide feedback control ofthe boundary and internal plasma parameters is demonstrated. It is shown that thecomplex allows investigating the processes in currently operated and designed fusiondevices and solving problems of fusion application for energy production. The recommendations to the engineering implementation of plasma control systems are made.The directions for further research are formulated.